Cohort profile: InTraUterine sampling in early pregnancy (ITU), a prospective pregnancy cohort study in Finland: study design and baseline characteristics. Issue 1 (31st January 2022) - Kvist, Tuomas; Sammallahti, Sara; Lahti-Pulkkinen, Marius; Cruceanu, Cristiana; Czamara, Darina; Dieckmann, Linda; Tontsch, Alina; Röh, Simone; Rex-Haffner, Monika; Wolford, Eiina; Reynolds, Rebecca; Eriksson, Johan; et al.
Abstract : Purpose: The InTraUterine sampling in early pregnancy (ITU) is a prospective pregnancy cohort study. The overarching aim of ITU is to unravel genomic, epigenomic, transcriptomic, endocrine, inflammatory and metabolic maternal-placental-fetal mechanisms involved in the programming of health and disease after exposure to prenatal environmental adversity, such as maternal malnutrition, cardiometabolic disorders, infections, medical interventions, mental disorders and psychosocial stress. This paper describes the study protocol, design and baseline characteristics of the cohort. Participants: We included 944 pregnant Finnish women, their partners and children born alive between April 2012 and December 2017. The women were recruited through the national, voluntary trisomy 21 screening between 9 +0 and 21 +6 gestational weeks. Of the participating women, 543 were screen positive and underwent fetal chromosomal testing. Test result of these women suggested no fetal chromosomal abnormality. Further, we recruited 401 women who were screen negative and who did not undergo fetal chromosomal testing. Findings to date: We have collected chorionic villi and amniotic fluid from the screen-positive women; blood, urine, buccal swabs and diurnal salivary samples from all women; blood and buccal swabs from all partners; and placenta, cord blood and buccal swabs from all newborns for analyses of the genome, epigenome, transcriptome, and endocrine, inflammatory and metabolic markers. These data are coupled with comprehensive phenotypes, including questions on demographic characteristics, health and well-being of the women and their partners during pregnancy and of the women and their children at the child's age of 1.7 and 3 years. Data also come from patient records and nationwide registers covering health, lifestyle and medication data. Future plans: Multiple layers of ITU data allow integrative data analyses, which translate to biomarker identification and allow risk stratification and understanding of the biological mechanisms involved in prenatal programming of health and disease.